Keabsahan Syarat Sah Perjanjian dalam Kontrak Elektronik Menurut UU ITE Perbandingan Hukum Indonesia dan Republik Ceko - Shella Fairuz Umami (Fakultas Hukum, 2026)
The development of information and communication technology has transformed legal relations in society, particularly in electronic transactions conducted through digital platforms. One of the legal instruments arising from this development is the electronic contract, which enables agreements between parties without direct physical interaction. In Indonesia, the validity of electronic contracts is regulated under Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 (ITE Law), which refers to the legal requirements of agreements under Article 1320 of the Indonesian Civil Code. However, legal issues still arise regarding the fulfillment of consent and the determination of when an electronic agreement becomes legally binding. This research aims to analyze the validity of electronic contracts in Indonesia based on the Indonesian Civil Code and the ITE Law, as well as to compare the regulation of electronic contracts in Indonesia and the Czech Republic through Directive 2000/31/EC on Electronic Commerce. This study uses normative legal research with statutory, conceptual, and comparative approaches. The results show that the validity of electronic contracts in Indonesia depends on the fulfillment of the legal requirements of agreements, namely consent, legal capacity, a certain object, and a lawful cause. Nevertheless, the ITE Law still lacks comprehensive provisions regarding electronic consent mechanisms, particularly in clickwrap agreements and automated transactions. Compared to the European Union framework applied in the Czech Republic, the regulation provides stronger legal certainty and consumer protection. Therefore, clearer and more adaptive regulations are needed to ensure legal certainty and protection in electronic transactions.
FINALISASI oleh Arif 2026 Mei 26
Keywords: Electronic Contract; Validity of Agreement; ITE Law; Civil Code; Electronic Transactions; Comparative Law.